2019
DOI: 10.1164/rccm.201806-1110oc
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiopulmonary Exercise Testing Provides Additional Prognostic Information in Cystic Fibrosis

Abstract: RATIONALE: The prognostic value of cardiopulmonary exercise testing (CPET) for survival in cystic fibrosis (CF) in the context of current clinical management, when controlling for other known prognostic factors is unclear. OBJECTIVES: To determine the prognostic value of CPET-derived measures beyond peak oxygen uptake (VO2peak) following rigorous adjustment for other predictors. MEASUREMENTS AND MAIN RESULTS: Data from 10 CF-centers in Australia, Europe and North America were collected retrospectively. 510 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
139
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(151 citation statements)
references
References 23 publications
(44 reference statements)
6
139
0
Order By: Relevance
“…International groups support the completion of annual laboratory‐based exercise tests in people with CF . The results of this survey highlight the infrequent use of this type of exercise test in Australian and New Zealand CF centres.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…International groups support the completion of annual laboratory‐based exercise tests in people with CF . The results of this survey highlight the infrequent use of this type of exercise test in Australian and New Zealand CF centres.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding testing, international recommendations support the completion of annual laboratory‐based exercise testing (i.e. a cardiopulmonary exercise test (CPET)) to identify exercise intolerance, guide exercise prescription and for prognostication . Work done 15 years ago in the United Kingdom and Germany reported that annual CPET data were collected on less than 50% of CF people living with the uptake compromised by cost, the need for specialised equipment and technical expertise to conduct these tests with .…”
Section: Introductionmentioning
confidence: 99%
“…Exercise performance has long been known to be an independent predictor of mortality. In a retrospective multinational study of 433 children and adults with CF who performed CPET, VO2peak, VE/VO2, and VE/VCO2 were independently associated with death or lung transplant over a 10‐year period, even after adjustment for other risk factors including age at CPET, sex, BMI, CF‐related diabetes, and infection with PA . A cluster of patients with low pulmonary function, poor nutritional status, and abnormal CPET parameters were at particularly high risk of mortality.…”
Section: Physiological Assessmentmentioning
confidence: 99%
“…The cause of such reduction is multifactorial and includes impairments in lung function as well as peripheral and respiratory muscle deconditioning, the latter of which contributes to breathlessness and muscle fatigue during exercise [ 2 , 3 ]. In this population, as greater exercise capacity has been associated with better health-related quality of life (HRQoL) [ 4 , 5 ] and survival [ 6 , 7 , 8 ], maintaining or improving exercise capacity is an important treatment goal.…”
Section: Introductionmentioning
confidence: 99%